PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) PADA MATA KULIAH FILSAFAT SAINS - Irnin Agustina Dwi Astuti (Jurnal Pendidikan Fisika, 2016)
Critical thinking skills the students of Physical Education remains low. It is caused by several factors, including the learning process is not optimal. This study aims to determine the increase in critical thinking skills by learning model Problem Based Instruction (PBI). The method used is a classroom action research that includes planning, implementation, observation, and reflection. Data collections are done by observation, questionnaires, documentation, field notes and tests. Forms of data analysis used qualitative analysis. It can be concluded that the implementation of learning with Problem Based Instruction learning model can improve the critical thinking skills students in Philosophy of Science. This is evidenced by the increase in the average percentage of critical thinking skills of each cycle. In the first cycle, the average critical thinking skills students are 66.87%. In the second cycle into 80.19% or an increase of 13.32%. Thus the average percentage of critical thinking skills students has exceeded predetermined success criteria with the category is "very critical".